Process Evaluation of the Community Pharmacist-Led Allergic Rhinitis Management (C-PhARM) Service in Singapore - Joanne Shi Ying Yap; Colin Wei Qiang Tang; Helena Mei Ling Hor; Joy Boon Ka Chong; Kai Zhen Yap (MDPI AG, 2019)
A community pharmacist-led allergic rhinitis management (C-PhARM) service involving structured patient assessment, individualised recommendations and follow-up was developed in Watson’s Personal Care Stores Pte Ltd (Singapore) to ensure optimal allergic rhinitis (AR) self-management and appropriate use of intranasal corticosteroids (INC) in Singapore. This retrospective study aimed to evaluate the C-PhARM service processes and identify areas for improving the quality of service. Relevant data was extracted from archived clinical forms, customer satisfaction surveys and pharmacist quality improvement surveys to evaluate the “reach”, “recruitment”, “context” and “fidelity” of service implementation, as well as the “intervention delivered” and “received”. Over the nine months since the launch of the C-PhARM service in April 2016, 45 customers were enrolled, and 32 (71.1%) customers had received at least one follow-up. Recommendations provided at baseline included oral antihistamines (32, 71.1%), INC sprays (28, 62.2%) and counselling on non-pharmacological strategies (27, 60.0%). Among the 29 customers who exited the service, 20 (69%) responded to a satisfaction survey. Although customers deemed pharmacists to be professional and knowledgeable in providing clear and detailed information about AR, pharmacists reported a lack of protected time and interest from customers as service barriers. Sufficient protected time is required for pharmacists to effectively provide clinical service in a community pharmacy.